1970
DOI: 10.1002/pol.1970.150081007
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of monolayers of vinyl and divinyl monomers

Abstract: synopsisMonolayer balance techniques have been used to study "two-dimensional" polymerization of monomolecular films of octadecyl methacrylate and a divinyl ester. Polymerizations were initiated with ultraviolet radiation, and reaction rates and properties of the product evaluated from surface pressure-area isotherms. The polymerization rate of the acrylate in argon is linear up t o 70% conversion; the product obtained in this way exhibits an isotherm which may reflect the packing and orientation of the starti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 12 publications
1
20
0
1
Order By: Relevance
“…Unfortunately, little proof was provided in regard to the formation of a 2D cross-linked polymer. [110] Dubault et al irradiated the better defined monomers 41 and 42 and provided a more in depth characterization of the products that were obtained at the air/water interface. [111] A sharp rise in viscosity was observed after a certain irradiation time onwards for 42, whereas the increase was continuous for 41.…”
Section: Cross-linking In Monolayers At Air/liquid and Liquid/liquid mentioning
confidence: 99%
“…Unfortunately, little proof was provided in regard to the formation of a 2D cross-linked polymer. [110] Dubault et al irradiated the better defined monomers 41 and 42 and provided a more in depth characterization of the products that were obtained at the air/water interface. [111] A sharp rise in viscosity was observed after a certain irradiation time onwards for 42, whereas the increase was continuous for 41.…”
Section: Cross-linking In Monolayers At Air/liquid and Liquid/liquid mentioning
confidence: 99%
“…Research has therefore been in progress over the last few years to create model systems for these membranes through the build up of monolayers formed at the gas-water interface. Many investigators have already reported the polymerization of monolayers at the gas-water interface to form stable and ordered systems (1)(2)(3)(4)(5). Until now only the vinyl and acrylic functionalities have been used as polymerizable endgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, dilatation of monolayers of reactive compounds has been observed when molecules become larger as the result of reactions with substances dissolved in a substrate, upon oxidation of unsaturated compounds, and under specific polymerization conditions [17][18][19][20]. Usually, dilatation of monolayers of reactive compounds has been observed when molecules become larger as the result of reactions with substances dissolved in a substrate, upon oxidation of unsaturated compounds, and under specific polymerization conditions [17][18][19][20].…”
Section: Anomalous Reactivities Of Epoxy Oligomers In the Langmuir Momentioning
confidence: 99%